The tyrosine phosphatase SHP2 is required for cell transformation by the receptor tyrosine kinase mutants FIP1L1‐PDGFRα and PDGFRα D842V. Issue 3 (17th February 2014) - Noël, Laura A.; Arts, Florence A.; Montano-Almendras, Carmen P.; Cox, Luk; Gielen, Olga; Toffalini, Federica; Marbehant, Catherine Y.; Cools, Jan; Demoulin, Jean-Baptiste
Abstract : Activated forms of the platelet derived growth factor receptor alpha (PDGFRα) have been described in various tumors, including FIP1L1‐PDGFRα in patients with myeloproliferative diseases associated with hypereosinophilia and the PDGFRα D842V mutant in gastrointestinal stromal tumors and inflammatory fibroid polyps. To gain a better insight into the signal transduction mechanisms of PDGFRα oncogenes, we mutated twelve potentially phosphorylated tyrosine residues of FIP1L1‐PDGFRα and identified three mutations that affected cell proliferation. In particular, mutation of tyrosine 720 in FIP1L1‐PDGFRα or PDGFRα D842V inhibited cell growth and blocked ERK signaling in Ba/F3 cells. This mutation also decreased myeloproliferation in transplanted mice and the proliferation of human CD34 + hematopoietic progenitors transduced with FIP1L1‐PDGFRα. We showed that the non‐receptor protein tyrosine phosphatase SHP2 bound directly to tyrosine 720 of FIP1L1‐PDGFRα. SHP2 knock‐down decreased proliferation of Ba/F3 cells transformed with FIP1L1‐PDGFRα and PDGFRα D842V and affected ERK signaling, but not STAT5 phosphorylation. Remarkably, SHP2 was not essential for cell proliferation and ERK phosphorylation induced by the wild‐type PDGF receptor in response to ligand stimulation, suggesting a shift in the function of SHP2 downstream of oncogenic receptors. In conclusion, our results indicate that SHP2 is required for cell transformation and ERK activation by mutant PDGF receptors. Highlights: We mutated twelve potentially phosphorylated tyrosines of FIP1L1‐PDGFRα. We identified Y720 as a key residue for cell transformation by FIP1L1‐PDGFRα. Phosphorylated tyrosine 720 binds directly to the tyrosine phosphatase SHP2. SHP2 is required for ERK activation and transformation by FIP1L1‐PDGFRα and PDGFRαD842V.